Fundamentals of Entrepreneurship (ENT300) : Proposal Vignette Sdn. Bhd. / Hazimah Mohd Mohiyeddin … [et al.] - Mohd Mohiyeddin, Hazimah; Awang Omar, Dayang Nur Marziana; Baharin, Azilena Zureen; Wasli, Maslina; Abdullah, Siti Zulaikha (2013)
Vignette Sdn. Bhd. is partnership business is in form of enterprise which consists of five members. All partnerships have agreed as stated in agreement letter which the amount of capital, profit and loss will be divided as stated ratio. We had chosen this kind of business because it shows the equality and no one will discriminate as the profits and losses are equally divided in the end of the accounting period. In other way, the partnership is a perfect option to be taken because the shareholders will always sharing ideas and knowledge in order to gain profit and achieve high productivity time to time.